2020
DOI: 10.34172/ijhpm.2020.142
|View full text |Cite
|
Sign up to set email alerts
|

Why Do They Leave? Challenges to Retention of Surgical Clinical Officers in District Hospitals in Malawi

Abstract: Background: Low- and middle-income countries (LMICs) are the worst affected by a lack of safe and affordable access to safe surgery. The significant unmet surgical need can be in part attributed to surgical workforce shortages that disproportionately affect rural areas of these countries. To combat this, Malawi has introduced a cadre of non-physician clinicians (NPCs) called clinical officers (COs), trained to the level of a Bachelor of Science (BSc) in Surgery. This study explored the barriers and enablers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Retention is associated with working conditions, availability of equipment and resources, ability to provide quality care, salary, opportunities for career progression, housing availability and quality (where housing is provided) as well as the feeling of being valued by colleagues. [58][59][60] Addressing these issues is multifaceted and requires significant investment from national government.…”
Section: Discussionmentioning
confidence: 99%
“…Retention is associated with working conditions, availability of equipment and resources, ability to provide quality care, salary, opportunities for career progression, housing availability and quality (where housing is provided) as well as the feeling of being valued by colleagues. [58][59][60] Addressing these issues is multifaceted and requires significant investment from national government.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in neighbouring countries of South Africa found that professional recognition, suitable employment options, opportunities for further studies and career paths that follow a multi-sector approach are significant in supporting cadres like ClinAs in healthcare facilities where they are needed most. 36,37,38 The creation of posts for ClinAs with postgraduate qualifications and their employment in these specialist posts are key to having more career paths opportunities for ClinAs, promoting them to higher posts and retaining them in the health system, particularly the public sector.…”
Section: Discussionmentioning
confidence: 99%
“…Tradition holds that the best academic medical centers the world over exist in urban environments, often leaving rural communities to rely on aid-based, unilateral programs for support. This can lead to an unintentional domestic brain drain whereby healthcare providers either want to or have to leave their communities for these urban centers to find the opportunities they have worked so hard to obtain (Gajewski et al, 2020). And again, while this challenge is not unique to LMICs by any means, the consequences of this centralization of services can be devastating for the communities that are unable to access such services.…”
Section: Centralization Of Servicesmentioning
confidence: 99%